Improving patient safety with triple-scan technology for insulin pen administration - Courtney K Wulffson; Melissa M Babin; Merissa T Andersen Pinotti (American Journal of Health-System Pharmacy, 2026)
Abstract Purpose High-alert medications such as insulin pose serious risks to patients when used in error. In response to vulnerabilities identified in existing insulin administration workflows, we implemented a comprehensive approach to mitigate the risk of errors in the hospital setting. Summary A new electronic health record capability, referred to as the “triple-scan system,” was introduced to enhance insulin pen administration safety. This system requires nurses to scan the patient’s wristband barcode, the insulin pen manufacturer’s barcode, and the pharmacy’s linking label barcode applied to the pen before it is retrieved from an automated dispensing machine. Other measures were also implemented to prevent errors, including a 2-nurse verification process and visual aids. A performance dashboard was used to track insulin pen administration. After the triple-scan system was integrated into workflows, the performance dashboard showed increasing numbers of barcodes scanned over a period of 4 months, whereas the number of unscanned barcodes remained low. Postimplementation surveys of 174 nurses indicated high satisfaction with the new system, with 67% (n = 116) reporting improved patient safety and 71% (n = 124) finding it user friendly. Conclusion The triple-scan system ensures the use of a single insulin pen for each patient, which may enhance patient safety by helping to prevent exposure to blood-borne pathogens. Engaging nurses as essential stakeholders and providing ongoing support and training were critical to the success of this intervention. Continuous monitoring and improvements are necessary to ensure the long-term sustainability of the triple-scan system.